2021
DOI: 10.7759/cureus.15480
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series of Multiple Primary Malignancies Among Patients With Advanced Melanoma

Abstract: Multiple primary malignancies (MPM) are described as two or more primary tumors within the same individual. The impact of MPM on the tumor microenvironment among patients with melanoma is poorly understood. Here, we describe this unique group of patients who have both advanced melanoma and at least one other primary malignancy and report their survival outcomes. In this study, patients with advanced melanoma and a second primary malignancy were identified. Medical records were reviewed for cancer treatment his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A case series including patients with advanced melanomas and one or more other nonmelanoma oncological diseases explored the choice of therapeutic strategies employed for the melanocytic tumors, as well as for the non-cutaneous malignancies [22]. Concerning the treatment strategies used for melanoma, the majority of patients (90.9%) underwent surgery, systemic therapy including immunotherapy, targeted therapy and cytotoxic chemotherapy (81.8%) and a minority of them was exposed to radiation therapy (9.1%) [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A case series including patients with advanced melanomas and one or more other nonmelanoma oncological diseases explored the choice of therapeutic strategies employed for the melanocytic tumors, as well as for the non-cutaneous malignancies [22]. Concerning the treatment strategies used for melanoma, the majority of patients (90.9%) underwent surgery, systemic therapy including immunotherapy, targeted therapy and cytotoxic chemotherapy (81.8%) and a minority of them was exposed to radiation therapy (9.1%) [22].…”
Section: Discussionmentioning
confidence: 99%
“…A case series including patients with advanced melanomas and one or more other nonmelanoma oncological diseases explored the choice of therapeutic strategies employed for the melanocytic tumors, as well as for the non-cutaneous malignancies [22]. Concerning the treatment strategies used for melanoma, the majority of patients (90.9%) underwent surgery, systemic therapy including immunotherapy, targeted therapy and cytotoxic chemotherapy (81.8%) and a minority of them was exposed to radiation therapy (9.1%) [22]. A total of 54.5% of the patients received immune checkpoint inhibitors such as PD-1 and CTLA-4 inhibitors [22] and previous studies demonstrated that, even though the efficacy of these agents is significant on first primary melanomas, their interference with the development of second primary melanocytic malignant tumors or other non-cutaneous cancers remains controversial [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the patient had pulmonary sarcomatoid carcinoma detected in the liver, it was also supported by the results of the IMpower 150 trial, in which the subgroup with previous liver metastasis had a median overall survival gain of four months, with ABCP ( Socinski et al 2021 ). The efficacy of immunotherapy in patients with multiple primary cancers is limited but one case series of patients with multiple primary malignancies with advanced melanoma showed that six out of 11 patients had complete response to immunotherapy ( Ebia et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%